Exploring the microbiome-gut-testis axis in testicular germ cell tumors - Sona Ciernikova; Aneta Sevcikova; Michal Mego (Frontiers in Cellular and Infection Microbiology)
The microbiome-gut-testis axis has emerged as a significant area of interest in understanding testicular cancer, particularly testicular germ cell tumors (TGCTs), which represent the most common malignancy in young men. The interplay between the gut and testicular microbiomes is hypothesized to influence tumorigenesis and reproductive health, underscoring the complex role of microbial ecosystems in disease pathology. The microbiome-gut-testis axis encompasses complex interactions between the gut microbiome, systemic immune modulation, and the local microenvironment of the testis. Dysbiosis in the gut or testicular microbiomes may contribute to altered immune responses, inflammation, and hormonal imbalances, potentially playing a role in the pathogenesis of TGCTs. Concurrently, seminal microbiomes have been linked to variations in sperm quality, fertility potential, and possibly cancer susceptibility, underscoring the need for further evaluation. This review explores the emerging role of the microbiome-gut-testis axis in the context of testicular cancer, highlighting its implications for disease onset, progression, treatment efficacy, and toxicity. Identifying potential microbial biomarkers, followed by microbiota modulation to restore a balanced microbial community, might offer a novel supportive strategy for improving treatment efficacy in refractory TGCT patients while reducing chemotherapy-induced toxicity. We suggest a better understanding of the association between dysregulated microbial environments and TGCTs emphasizes potential pathways by which the gut microbiome might influence testicular cancer.